Climate interacts with anthropogenic drivers to determine extirpation dynamics. Issue 10 (14th January 2016) - Comte, Lise; Hugueny, Bernard; Grenouillet, Gaël
Abstract : Theoretical studies suggest that the dynamics of a species' range during a period of climate change depends upon the existence and interplay of various ecological and evolutionary processes. Here we tested how anthropogenic pressures contribute to climate‐mediated extirpation patterns of 32 freshwater fish species over the last 20 yr. We contrasted two extreme cases to determine whether extirpations were governed by patterns of climate exposure, assuming full adaptation of species to local climate, or instead by the interplay between climate exposure and the distance from the centroid of species' climatic niches, assuming a fixed niche, and asked whether anthropogenic disturbances interact with these climatic drivers. We found strong support for the fixed niche hypothesis, but showed that species‐specific local adaptation to climate may also be important in determining extirpation dynamics. We also demonstrated that anthropogenic disturbance acted in concert with climate, ultimately determining population changes. Our results add novel evidence that unravelling the direct links between range dynamics and climate requires a multifaceted treatment, and that accounting for the cumulative effects of anthropogenic pressures deserves special attention in the context of climate change.